Data underpinning research article "Optimising Renewable Energy Integration in New Housing Developments with Low Carbon Technologies" - Chowdhury, Jahedul; Balta-Ozkan, Nazmiye; Hart, Phil; Varga, Liz; Hu, Yukun (Cranfield University, 2021)
This file includes data for energy demand and generation profile for different house types in the UK. It also contains data for daily average solar irradiance for typical UK weather conditions that were used for calculating PV outputs.
Keywords: New housing developments'; 'Solar PV'; 'Renewable energy sources (RES)'; 'Electric vehicles (EVs)'; 'battery storage systems'; 'Grid impacts'; 'Energy Generation; Conversion and Storage Engineering'; 'Renewable Power and Energy Systems Engineering (excl. Solar Cells)'